E-blood banking information system (EBBIS) - Nur Amirah, Rahmat (2016)
Blood is one of the important element in our body and it occupy around seven percent out of our body weight. It plays important role in our body like carry the oxygen to our whole body, giving protection in inflammation and regulation in our body PH level. For those who lack of blood will facing healthy problem. Thus, we need to donate our blood to the people who need it. E-Blood Banking Information System (EBBIS) is an online management system which will run in the website to manage the blood bank information, blood donor information, blood donation appointment and blood request facility. The purpose of this study is to create online blood bank system and appropriate method of applying EBBIS. All the related information regarding the system is studied. RAD is the development methodology that being used for the development of the system. This method will act as a guide for me when developing this system. This methodology is chosen because it allows me to create this system in a limited time. Functionality of the system is done using the sample test detail. User Acceptance Test have been applied in ensuring the acceptance of user to the system. The system have been accepted by the user where in general they are satisfied with the functionality and benefit derived from the system. Last but not least, the output of this study is e-Blood Banking Information System (EBBIS).